Emerging and potentially emerging viruses in water environments - Giuseppina La Rosa; Marta Fratini; Simonetta della Libera; Marcello Iaconelli; Michele Muscillo (Istituto Superiore di Sanità, 2012)
Among microorganisms, viruses are best fit to become emerging pathogens since they are able to adapt not only by mutation but also through recombination and reassortment and can thus become able to infect new hosts and to adjust to new environments. Enteric viruses are among the commonest and most hazardous waterborne pathogens, causing both sporadic and outbreak-related illness. The main health effect associated with enteric viruses is gastrointestinal illness, but they can also cause respiratory symptoms, conjunctivitis, hepatitis, central nervous system infections, and chronic diseases. Non-enteric viruses, such as respiratory and epitheliotrophic viruses are not considered waterborne, as they are not readily transmitted to water sources from infected individuals. The present review will focus on viral pathogens shown to be transmitted through water. It will also provide an overview of viruses that had not been a concern for waterborne transmission in the past, but that may represent potentially emerging waterborne pathogens due to their occurrence and persistence in water environments.